FveARF2 negatively regulates fruit ripening and quality in strawberry - Yi, Shan-na; Mao, Jian-xin; Zhang, Xin-yu; Li, Xiao-ming; Zhang, Zhi-hong; Li, He (Frontiers in Plant Science, 2022)
The ARFs family is typical transcription factors that play important roles in plants growth and development process. However, the role of FveARF2 in the formation of strawberry fruit quality remains unclear. In this study, FveARF2 was isolated from the woodland strawberry ‘Ruegen’. FveARF2 was highly expressed in stem and fruit at white stage. Subcellular localization analysis showed that FveARF2 was located in the nucleus. Transactivation analysis showed that FveARF2 presented transcriptional inhibition activity in yeast. Silencing of FveARF2 in cultivated strawberry fruits revealed earlier coloring and higher sweetness in the transgenic fruits compared with the wild-type, and opposite phenotypes were found in FveARF2-OE fruits. Gene expression analysis indicated that the transcription levels of fruit ripening genes FaSUT1, FaOMT and FaCHS were increased in FveARF2-RNAi fruits, and decreased in FveARF2-OE fruits, both compared with the wild-type. Furthermore, FveARF2 could directly bind to the AuxRE (TGTCTC) element in FaSUT1, FaOMT and FaCHS promoters in vitro and vivo. Potassium ion supplementation could improve the quality of strawberry fruit and silencing FveARF2 could increase potassium ion content in transgenic fruits. Yeast one-hybrid and GUS activity experiment also proved FveARF2 could directly bind to the promoter of FveKT12, a potassium transporter gene, and inhibited its expression. Taken together, our study found that FveARF2 can affect fruit ripening and quality through regulate the expression of ripening related genes and the potassium ion transport gene.